CLAIMS FOR PAYMENT OF ADMINISTRATIVE APPLICATION WORKSHOP ON CARS MITRA USING VISUAL BASIC 6.0 PROGRAMMING - Dewi Maelawati; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2003)
In writing this study, the authors tried to explain about the payment of administrativeapplications in a car repair shop, where the garage is a car repair and maintenanceplaces, and usually for customers who've never fix his car in the garage will be givena receipt of payment in the form of invoice payments.The problems that the authors try to describe is that the workshop which in theservice manual is still facing many difficulties in seeking customer data, so theservice provided to customers is still not quick enough in the process. Anotherproblem also arises in terms of data storage that is consuming the place, where thenumber of customers who came to fix the car more and more, so that data records arealso increasingly numerous improvements.